Effect of an ac electric field on weak electron localization in Bi films - Belevtsev, B.I.; Hasse, J.; Anopchenko, A.S.; Beliayev, E.Yu. (Физика низких температур, 1996)
We have studied the effects of weak localization and electron-electron interaction in the conductivity of Bi films at temperatures between 1.1 and 4.2 К in the presence of a high-frequency electric field ( - 9.4 GHz). The experiments were carried out under conditions of no appreciable overheating of electrons due to a microwave radiation. The data obtained permit us to examine the influence of temperature on quantum corrections Δδ(Ω) at high-frequency electric field more comprehensively and reliably than in earlier works. The experimental dependences Δδ(Ω, T) are found to be in good agreement with the known theoretical models.